Massively Parallel Sequencing of a Chinese Family with DFNA9 Identified a Novel Missense Mutation in the LCCL Domain of COCH. (27th December 2016) - Gu, Xiaodong; Su, Wenling; Tang, Mingliang; Guo, Luo; Zhao, Liping; Li, Huawei
Abstract : DFNA9 is a late-onset, progressive, autosomal dominantly inherited sensorineural hearing loss with vestibular dysfunction, which is caused by mutations in the COCH (coagulation factor C homology) gene. In this study, we investigated a Chinese family segregating autosomal dominant nonsyndromic sensorineural hearing loss. We identified a missense mutation c.T275A p.V92D in the LCCL domain of COCH cosegregating with the disease and absent in 100 normal hearing controls. This mutation leads to substitution of the hydrophobic valine to an acidic amino acid aspartic acid. Our data enriched the mutation spectrum of DFNA9 and implied the importance for mutation screening of COCH in age related hearing loss with vestibular dysfunctions.